PENGARUH TINGKAT KEPADATAN POPULASI AYAM BROILER (Gallus sp.) DALAM KANDANG TERHADAP HIPERTROFI SEL KORTEKS ADRENAL (Influence of Population Density of Broiler Chickens (Gallus sp.) in Cages to the Hypertrophy of Adrenocortical Cells) - Hamdani Budiman; Sugito Sugito; Widya Nanda; Muhammad Hanafiah; Muhammad Nur Salim; Ismail Ismail (Universitas Syiah Kuala, 2015)
The purpose of this study was to determine the effect of population density of broiler chickens (Gallus sp.) in the cages to the hypertrophy of adrenocortical cells. This study was conducted using complete randomized design (CRD) with 84 broiler chickens. All chickens were divided into 4 groups with 3 replications. Each group consists of 4 chickens (K1), 6 chickens (K2), 8 chickens (K3), and 10 chickens (K4). Chickens were rear from aged of 2 days up to 35 days. The histopathological examination of adrenal glands were performed by collected the adrenal glands of chickens then proceed to histopathological method and stained with haematoxylin eosin (HE). The percentage of hypertrophy of adreno cortical cells was calculated. The results of statistical analysis showed that the population densities of broiler chickens had highly significant effect (P0.01) to the histopathology of adrenal gland. The highest average of hypertrophy was found in K4. To conclude, the highest the dense population of broiler chickens in the cage, the highest the number of hypertrophy of adenocortical cells.Key words: population density, hypertrophy of adrenocortical cell